1997
DOI: 10.1021/la970450d
|View full text |Cite
|
Sign up to set email alerts
|

Micellization and Micellar Structure of a Poly(ethylene oxide)/Poly(propylene oxide)/Poly(ethylene oxide) Triblock Copolymer in Water Solution, As Studied by the Spin Probe Technique

Abstract: The micellization of the triblock copolymer Pluronic P85 (poly(oxyethylene)27/poly(oxypropylene)39/poly(oxyethylene)27) in aqueous solution was followed vs temperature and addition of aliphatic alcohols, using the spin probe technique. Different types of probes properly chosen (spin-labeled (SL) poly(oxyethylene(4))nonylphenol, SL-Pluronic L62, TEMPO-laurate, TEMPO-hexanoate, CAT 4, CAT 8, CAT 11, CAT 16, and 5-, 7-, 10-, and 12-doxylstearic acids) provided information about the micellar structure (polarity, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 37 publications
3
114
0
Order By: Relevance
“…This would be consistent with the fact that several different surface-active compounds were able to cause the large increase in the concentrations of the alcohol and monoester. Alcohols have been shown to interact closely with surfactants in an aqueous medium (Caragheorgheopol et al 1997;Lin and Jiang 1997). In particular, they have been shown to form mixed micelles with surfactant molecules and subsequently change the surface chemistry of the mixture (Patist et al 1998;Marangoni and Kwak 1991;Bockstahl and Duplatre 2001;Akhter and Al-Alawi 2000;Trotta et al 1993;Su et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This would be consistent with the fact that several different surface-active compounds were able to cause the large increase in the concentrations of the alcohol and monoester. Alcohols have been shown to interact closely with surfactants in an aqueous medium (Caragheorgheopol et al 1997;Lin and Jiang 1997). In particular, they have been shown to form mixed micelles with surfactant molecules and subsequently change the surface chemistry of the mixture (Patist et al 1998;Marangoni and Kwak 1991;Bockstahl and Duplatre 2001;Akhter and Al-Alawi 2000;Trotta et al 1993;Su et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Above the CMT, the micellar size generally increases progressively with an increase in temperature before the solution phase separates at the cloud point (CP). The influence of temperature [8][9][10][11][12], various watersoluble electrolytes [13][14][15][16][17], and solvents [18][19][20] on the selfassembly behaviour of these copolymers in water has previously been reported. On approaching the cloud point many of these copolymer micellar solutions exhibit sphere to rod transitions [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 96%
“…Using NMR and fluorescence-quenching studies, Almgren et al [21] showed that the surfactant induces the micellization at low concentrations of Pluronics (below the CMC) and forms mixed micelles thereafter. A limited numbers of studies on the 0021-9797/$ -see front matter © 2007 Elsevier Inc. All effect of the addition of cosolvents such as alcohols and highly polar solvents such as glycerol, propylene glycol, and other glycols on the phase behaviour of Pluronics have been reported [18][19][20]. The different glycols locate in different microdomains of Pluronic and can change the interfacial properties; the ability of this molecule has been studied and reported [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in hydrodynamic size may be accounted for by increased shell thickness due to higher solvation of the PEO blocks in the [23]. Addition of higher chain alcohols, replaces the water surrounding of the PPO block, and an interaction between the alkyl chain of alcohol and PPO segments may take place [24]. The location of solubilized alcohol is in the core and/ or the palisade layer of the micelles, due to the relatively less polar nature of the higher alcohol would decrease the water content in the micellar core and increase the hydrophobicity which leads to an enhanced propensity of the sphere-to-rodlike transition particularly on approaching the cloud point.…”
Section: Resultsmentioning
confidence: 99%